2015
DOI: 10.1111/odi.12330
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapy reduces gelatinolytic activity in the rat trigeminal ganglion during temporomandibular joint inflammation

Abstract: Low-level laser therapy could constitute an adjuvant therapy to treat temporomandibular disorders and prevent inflammation-induced alterations in the levels of MMP-2 and MMP-9 and in the gelatinolytic activity in TGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
1
10
0
7
Order By: Relevance
“…In experimental wound healing studies, photobiomodulation has been reported to improve rates of healing (less time for wound closure), collagen formation, wound tensile strength, and flap survival. 12 It was also shown to resolve inflammation, 13 reduce the pain associated with chronic neuropathic lesions and chronic joint disorders, 12,[14][15][16][17] and reduce acute soft tissue injury edema after second-degree ankle sprain, 18 compared with standard care (rest, ice compress application, and elevation). Positive outcomes (ie, reduction of pain, improved function, faster recovery, and circulating concentrations of markers for inflammation and muscle damage) have been associated with photobiomodulation therapy for diseases such as osteoarthritis, tendinopathies, wounds, muscle fatigue, and various neurologic dysfunctions 19,20 in human clinical trials.…”
Section: Ivddmentioning
confidence: 99%
“…In experimental wound healing studies, photobiomodulation has been reported to improve rates of healing (less time for wound closure), collagen formation, wound tensile strength, and flap survival. 12 It was also shown to resolve inflammation, 13 reduce the pain associated with chronic neuropathic lesions and chronic joint disorders, 12,[14][15][16][17] and reduce acute soft tissue injury edema after second-degree ankle sprain, 18 compared with standard care (rest, ice compress application, and elevation). Positive outcomes (ie, reduction of pain, improved function, faster recovery, and circulating concentrations of markers for inflammation and muscle damage) have been associated with photobiomodulation therapy for diseases such as osteoarthritis, tendinopathies, wounds, muscle fatigue, and various neurologic dysfunctions 19,20 in human clinical trials.…”
Section: Ivddmentioning
confidence: 99%
“…Assim, aoobservarmos através do teste de von Frey que houve reversão total do limiar nociceptivo, concluímos que o laser de baixa intensidade foi efetivo no controle da dor articular. Acreditamos que este método seria mais adequado para avaliar a dor na ATM pois estepermite quantificar a alodinia e delimita a sua localização.Outros testes são utilizados para a avaliação do fenômeno doloroso na região orofacial, como aquele quemensura o comportamento nociceptivoatravés da contagem de movimentos de esfregacoscom a pata dianteira ou traseira ipsilateral na região operada (assimétrica) e os movimentos de balanceio da cabeça, no período de recuperação pos-anestésica por 45 minutos (Levin et al, 1978;Jacobs et al, 2002;Sydney;Conti, 2011;Barretto et al, 2013;Desiderá et al, 2015).…”
Section: Discussionunclassified
“…A participação da SP no processo nociceptivo advém de estudos em animais, os quais mostraram quantidades alteradas de SP no tecido lesado (Sahbaie et al, 2009 (Levin et al, 1978;Jacobs et al, 2002;Sidney;Conti, 2011;Barretto et al, 2013;Desiderá et al, 2015).…”
Section: Transmissão Nociceptiva Da Região Orofacialunclassified
“…De fato, a LLLT reduz a alodinia mecânica e a hiperalgesia orofacial de ratos com inflamação persistente da ATM, bem como de marcadores inflamatórios no gânglio trigeminal (DESIDERÁ et al, 2015). Outro estudo em modelo animal demonstrou os mecanismos de ação da laserterapia, que atuam na formação do edema, na permeabilidade vascular e na redução da hiperalgesia, atenuando desta forma o processo inflamatório e a dor.…”
Section: Muitas Modalidades De Tratamento Têm Sido Descritas Para O Munclassified
“…Muitos fatores podem determinar a magnitude do efeito placebo: diferenças individuais, fatores psicológicos, experiências prévias com a terapia testada, postura profissional, relação profissional-paciente, ambiente de terapia, e muitos outros (OKEN, 2008 Portanto, a LLLT é capaz de promover efeitos biológicos nos tecidos aplicados como já demonstrado em estudos com modelos animais (IYOMASA et al, 2013;SILVEIRA et al, 2013;DESIDERÁ et al, 2015), porém em seres humanos os aspectos cognitivos, comportamentais e motivacionais que permeiam o efeito placebo são tão significativos na percepção de melhora da dor crônica quanto estes efeitos biológicos demonstrados, pois levam a resultados clínicos muito semelhantes, o que não significa dizer que a LLLT não funcione.…”
Section: Efeito Placebounclassified